Association of TNF-α genetic variants with neonatal bronchopulmonary dysplasia: consolidated results - Shams, Seyedeh Elham; Dastgheib, Seyed Alireza; Mousavi-Beni, Seyede Arefe; Hosein Lookzadeh, Mohamad; Mirjalili, Seyed Reza; Golshan-Tafti, Mohammad; Bahrami, Reza; Yeganegi, Maryam; Shahbazi, Amirhossein; Masoudi, Ali; Shiri, Amirmasoud; Noorishadkam, Mahmood; et al. (Frontiers in Pediatrics, 2024)
ObjectivesInflammation is increasingly recognized as a key factor in the pathophysiology of bronchopulmonary dysplasia (BPD). While previous research has established significant links between TNF-α polymorphisms and BPD susceptibility, further validation of these associations is needed. This study aims to examine the relationship between TNF-α polymorphisms and the risk of BPD.MethodsAll relevant articles published before October 1, 2024, have been screened in the PubMed, Web of Science, CNKI, and Scopus databases.ResultsA total of 14 case-control studies were conducted: five studies with 1,252 cases and 1,377 controls on −308G/A, three studies with 1,180 cases and 1,194 controls on −238G/A, four studies with 149 cases and 192 controls on −857C/T, and two studies with 82 cases and 162 controls on 1,031 T/C. A significant association was found between the TNF-α −238G/A polymorphism and the risk of BPD. However, no significant relationships were observed for the TNF-α −308G/A, −857C/T, and 1,031 T/C polymorphisms regarding BPD susceptibility.ConclusionsOur findings indicate a significant association between the TNF-α −238G/A polymorphism and the susceptibility to BPD in preterm neonates, suggesting potential biomarkers for its pathogenesis. However, this meta-analysis has limitations, including possible publication bias and heterogeneity due to the limited number of studies, which may affect the reliability of our conclusions. Moreover, population variability further complicates the interpretation of the link between TNF-α polymorphisms and BPD risk.